Taxonomic notes on Euglossa (Glossuropoda) with a key to the known species (Hymenoptera: Apidae: Euglossina) - Nemésio, André (Zootaxa, 2009)
Euglossa hugonis Moure, 1989, described from the municipality of Tabatinga, state of Amazonas, Brazil, and Euglossa juremae Moure, 1989 described from the municipality of Vigia, state of Pará, Brazil, were recently considered to be the same species and synonymized under the former nomen. Through examination of both holotypes, I here show that both forms are distinct species. Additionally, it is strongly suggested that Euglossa hugonis and Euglossa rugilabris Moure, 1967 are the same species, and E. hugonis (syn. n.) is here considered a junior synonym of E. rugilabris. A synonymic list of all species of Euglossa (Glossuropoda) is presented, as well as the first identification key for the species of this subgenus.